Changes in land use and land cover and cocoa production in relation to gold mining in the Amansie West district, Ghana - Blankson, Anastasia Comfort (KNUST, 2026)
A thesis submitted to the department of theoretical and applied biology, kwame nkrumah university of science and technology in partial fulfilment of requirements for the award of Master of Philosophy degree in Environmental Science